Key Technologies of Tunnel Firefighting Robots. Issue 1 (2nd January 2017) - Wang, Yong; Xing, Jin-Peng; Guo, Hui; Wang, Li-Jing
ABSTRACT: For fire rescue difficulties in tunnels, and some other types of buildings, a review of key technologies and research into tunnel firefighting robots is given in this paper. Specifically, the key technical issues such as: the mechanical design; drive system design; control systems; and the anti-jamming system of tunnel firefighting robots are discussed. Also, the future development of the tunnel firefighting robots is discussed in this paper.